BIOCHEMISTRY IN THE SPECIALTY IN VISUAL FUNCTION, AND VIRTUAL ENVIRONMENTS IN THE CICS UMA-IPN - Magaña, Blanca Elisa Pérez (Universidad Autónoma Indígena de México, 2018)
The higher education and postgraduate in Mexico." delivered at the National Polytechnic Institute is located in a period of constant modification and sustained that has led to the creation of new pedagogical proposals aimed at the promotion of learning emphasizing virtual education. The development of ICT (Information Technologies and Communication) in the last few years has favored the emergence and consolidation of degrees, diplomas, Specialties, Master's Degrees among other, using the distance learning based on a web environment. This work analyzes the importance that had the Biochemistry course taught in the specialty of Visual Function in the CICS and UMA that allowed both to the students as the teachers try to virtually eliminate the disadvantages theoretical to traditional teaching. The results obtained in addition to the skills and competences acquired the students were highly successful, and it is hoped to be able to continue implementing such environments in other specialties and master's degrees.